2020
DOI: 10.1002/jia2.25586
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to HIV antiretroviral therapy among pregnant and postpartum women during the Option B+ era: 12‐month cohort study in urban South Africa and rural Uganda

Abstract: Introduction We conducted a cohort study to understand patterns of anti‐retroviral therapy (ART) adherence during pregnancy, postpartum and non‐pregnancy follow‐up among women initiating ART in public clinics offering Option B+ in rural Uganda and urban South Africa. Methods We collected survey data, continuously monitored ART adherence (Wisepill), HIV‐RNA and pregnancy tests at zero, six and twelve months from women initiating ART in Uganda and South Africa, 2015 to 2017. The primary predictor of interest was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 75 publications
(81 reference statements)
0
17
0
Order By: Relevance
“…During the peripartum period, women living with HIV (WLWH) need to optimize both maternal child health (MCH) and HIV care. Several studies have found waning ART adherence postpartum and suboptimal viral suppression in cohorts of peripartum women [5][6][7]. Qualitative studies note that women desire peripartum support and encouragement, both for MCH and for HIV care [8][9][10].…”
Section: Introductionau : Pleaseconfirmthatallheadinglevelsarerepresentedcorrectlymentioning
confidence: 99%
“…During the peripartum period, women living with HIV (WLWH) need to optimize both maternal child health (MCH) and HIV care. Several studies have found waning ART adherence postpartum and suboptimal viral suppression in cohorts of peripartum women [5][6][7]. Qualitative studies note that women desire peripartum support and encouragement, both for MCH and for HIV care [8][9][10].…”
Section: Introductionau : Pleaseconfirmthatallheadinglevelsarerepresentedcorrectlymentioning
confidence: 99%
“…adherence to ART continue to undermine the health of WLWH and increase the risk of HIV transmission to infants and uninfected partners [2][3][4][5].…”
mentioning
confidence: 99%
“…Several determinants of non-adherence to ART in the general population or designated populations in South Africa have been proposed. These include psychosocial factors such as stigma, alcohol abuse, and mental health; socio-economic factors such lack of information, unemployment, long distance from clinics; drug toxicities, and deficiencies in the health system such as drug stock-outs and inadequate patient management [ 50 54 ]. The significant adversity from non-adherence is highlighted in a model analysis which predicts a spike in HIV infections in South Africa if a decrease in adherence is coupled with an increase in the rate of loss to follow-up in the test and treat programme [ 55 ].…”
Section: Resultsmentioning
confidence: 99%